Optimalisasi Potensi UMKM Kelurahan Sumurrejo Kecamatan Gunungpati melalui Digital Marketing Lumpur - Tri Sri Noor Asih; Sugianto Sugianto; Dwi Yulianti; Siti Harnina Bintari (Universitas Negeri Semarang, 2024)
Sumurrejo, Gunungpati, is one of the fostered villages of the Mathematics and Natural Sciences Faculty, Universitas Negeri Semarang, which is located about 8 kilometers from the Unnes Sekaran Campus. This village has several potentials, including UMKM for making tempeh which have been fostered by FMIPA for the last three years. This village is geographically quite strategic because it is traversed by inter-district roads which are quite busy. Seeing the potential and current technological changes, UMKM in Sumurrejo can continue to be developed through digital media. One of the solutions offered by the FMIPA Unnes community service team is through digital marketing socialization and training on the creation and management of online stores. In this activity, socialization was carried out to all UMKM owners in Sumurrejo, as well as training on the creation of an online store for youth organizations in Sumurrejo. The online shop managed by youth organizations is expected to be able to become a job for local youth and help marketing UMKM products in Sumurrejo.